2019
DOI: 10.1039/c8ay02087f
|View full text |Cite
|
Sign up to set email alerts
|

A LC-MS/MS method for simultaneous estimation of a novel anti-diabetic combination of saxagliptin and dapagliflozin using a polarity switch approach: application to in vivo rat pharmacokinetic study

Abstract: First LC-MS/MS method for the simultaneous determination of SAX and DAP. The method offers good sensitivity with LLOQ of 0.2 ng mL−1 for SAX and 5 ng mL−1 for DAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…A solid phase extraction procedure was applied for sample clean-up. The technique demonstrated high linearity in the range of 0.2 to 80 ng/mL for SAX and 5 to 2000 ng/mL for DAP [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A solid phase extraction procedure was applied for sample clean-up. The technique demonstrated high linearity in the range of 0.2 to 80 ng/mL for SAX and 5 to 2000 ng/mL for DAP [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intern, which consists of saxagliptine and dapagliflozin, is a combination medication for treating type 2 diabetes that has been approved by regulatory organizations. [5] Many HPLC [9][10][11][12][13] and a handful of LC-MS [6][7][8] techniques have been revealed for determining both medications separately and in combination. Phanindra [6] et al and Shruti [7] et al did not use deuterated substances as an internal standard in their published procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Many HPLC [9][10][11][12][13] and a handful of LC-MS [6][7][8] techniques have been revealed for determining both medications separately and in combination. Phanindra [6] et al and Shruti [7] et al did not use deuterated substances as an internal standard in their published procedures. Swapna et al reported a lengthy and laborious process for their liquid-liquid extraction approach.…”
Section: Introductionmentioning
confidence: 99%
“…Such sodium-glucose cotransporters are responsible for reabsorbing glucose into the kidney. [2,3] An extensive literature survey has revealed that there are few methods that are reported for estimation of SAXA and DAPA individually or in combination with other drugs by UV method, [4][5][6][7] reverse phase high performance liquid chromatographic (RP-HPLC) method, [8][9][10][11][12][13][14][15][16] tandem mass spectrometry method, [17] or LC-MS. [18,19] Hence, we propose to develop methods that are more reliable, sensitive, and simple for simultaneous estimation of SAXA and DAPA in bulk as well as a pharmaceutical formulation. In the present work, we developed and validated the UV method and RP-HPLC method for the simultaneous estimation of SAXA hydrochloride and DAPA in bulk drug and its formulation as per ICH guidelines Q2(R1).…”
Section: Introductionmentioning
confidence: 99%